2007
DOI: 10.1007/s00208-007-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Stably isomorphic dual operator algebras

Abstract: Abstract. We prove that two unital dual operator algebras A, B are stably isomorphic if and only if they are ∆-equivalent [7], if and only if they have completely isometric normal representations α, β on Hilbert spaces H, K respectively and there exists a ternary ring of operators M ⊂ B(H, K) such that α(A) = [M * β(B)M]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(78 citation statements)
references
References 7 publications
1
77
0
Order By: Relevance
“…The first assertion is discussed above (following from Theorem 2.8 and [5]). For the second, just as in the proof of this result from [5], Theorem 2.8 gives [8,17] 3. Some theory of w * -rigged modules 3.1.…”
Section: Theorem 28 If Y Is a Right W * -Module Over M And If Z Imentioning
confidence: 90%
See 1 more Smart Citation
“…The first assertion is discussed above (following from Theorem 2.8 and [5]). For the second, just as in the proof of this result from [5], Theorem 2.8 gives [8,17] 3. Some theory of w * -rigged modules 3.1.…”
Section: Theorem 28 If Y Is a Right W * -Module Over M And If Z Imentioning
confidence: 90%
“…[10,Chapter 4]) plays a considerable role in our paper. Indeed the absence of this tool, and also of a recently introduced module tensor product [17] (see also [8,Section 2]) is the main reason why headway was not made on this project many years ago.…”
Section: Introduction and Notationmentioning
confidence: 99%
“…Composing the map M ⊗ σh (X ⊗ σh Y) → X ⊗ σh Y above with the canonical map M × (X ⊗ σh Y) → M ⊗ σh (X ⊗ σh Y), one sees the action of M on X ⊗ σh Y is separately weak* continuous (see also [20]). That (a 1 a 2 )z = a 1 (a 2 z) for a i ∈ M, z ∈ X ⊗ σh Y, follows from the weak* density of X ⊗ Y, and since this relation is true if z is finite rank.…”
Section: Some Tensor Productsmentioning
confidence: 95%
“…We define X ⊗ σh M Y ⊗ σh N Z to be the quotient of X ⊗ σh Y ⊗ σh Z by the w * -closure of the linear span of terms of the form xm ⊗ y ⊗ z − x ⊗ my ⊗ z and x ⊗ yn ⊗ z − x ⊗ y ⊗ nz, with x ∈ X, y ∈ Y, z ∈ Z, m ∈ M, n ∈ N. By extending the arguments of Proposition 2.2 in [20] to the threefold normal module Haagerup tensor product, one sees that X ⊗ σh M Y ⊗ σh N Z has the following universal property: if W is a dual operator space and u : X × Y × Z → W is a separately w * -continuous, completely contractive, balanced, trilinear map, then there exists a w * -continuous and completely contractive, linear map…”
Section: Some Tensor Productsmentioning
confidence: 98%
“…In [16] it was shown that the -equivalence implies weak * Morita equivalence in the sense of [4]. That is, any of the equivalences of [15] is one of our weak * Morita equivalences.…”
Section: Introduction and Notationmentioning
confidence: 94%